2005
DOI: 10.1177/073724770503000205
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Third-Grade Mathematics Textbooks Before and After the 2000 NCTM Standards

Abstract: We previously conducted a curriculum analysis of third-grade mathematics textbooks aimed at investigating the extent to which teaching the recommended methods for problem solving adhered to the 2000 National Council of Teachers of Mathematics (NCTM) Standards and instructional design criteria. In this article, we extend the previous findings by comparing the teaching of problem solving presented in the same textbooks published after the 2000 NCTM Standards to that in older editions published before the Standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
(30 reference statements)
1
12
0
Order By: Relevance
“…In addition, textbooks should include sufficient, varied, and relevant opportunities for use and practice to promote skilled application and performance (Sood & Jitendra, 2007; Woodward & Montague, 2002). For developing representational ability, this would involve not only exposure to various representations within the content to be learned but also opportunities to generate representations, select among mathematical representations, and apply a representation provided to solve various mathematical tasks (Jitendra, Deatline-Buchman, & Sczesniak, 2005).…”
Section: Students With Disabilities and Their Representational Abilitymentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, textbooks should include sufficient, varied, and relevant opportunities for use and practice to promote skilled application and performance (Sood & Jitendra, 2007; Woodward & Montague, 2002). For developing representational ability, this would involve not only exposure to various representations within the content to be learned but also opportunities to generate representations, select among mathematical representations, and apply a representation provided to solve various mathematical tasks (Jitendra, Deatline-Buchman, & Sczesniak, 2005).…”
Section: Students With Disabilities and Their Representational Abilitymentioning
confidence: 99%
“…In general, it has been found that textbooks, regardless of instructional perspective, typically do not adequately support learners with disabilities (Bryant et al, 2008; Carnine et al, 1997; Jitendra et al, 1996; Jitendra, Deatline-Buchman, et al, 2005; Jitendra, Griffin, et al, 2005; Jitendra et al, 1999; Sood & Jitendra, 2007). Use of key instructional components such as explicit instruction and adequate opportunities for practice are lacking.…”
Section: Mathematics Textbooks and Content Related To Developing Reprmentioning
confidence: 99%
See 2 more Smart Citations
“…While a textbook does not fully reflect what happens in the classroom, it does however show the instructional objectives that can influence students' mathematical knowledge (Dumitraşcu, 2015). All these significant points have led studies to analyze textbooks under various subject areas in the mathematics education literature (Ashcraft & Christy, 1995;Bakılan-Mutu, 2008;Freeman & Porter, 1989;Jitendra, Deatline-Buchman, & Sczesniak, 2005;Kerpiç & Bozkurt, 2011;Tanışlı & Köse, 2011;Taşdemir, 2011;Yeniterzi & Işıksal-Bostan, 2015).…”
mentioning
confidence: 99%